The Expression of Recombinant Human Serum Albumin in the Mammary Gland of Transgenic Mice - Gui-Hua Gong; Shu Han; Xiao-Ling Huang; Li-Ping Xie; Wei Zhang; Lei Xu; You-Jia Hu (Pharmaceutical Fronts, 2021)
Human serum albumin (HSA) is widely used in the clinic for the treatment of several diseases in large amount each year. With the increasing demands of HSA in clinic and limited blood resource, recombinant HSA (rHSA) is becoming an attractive and alternative source for HSA production. In this study, we aimed to express rHSA in the mammary glands of transgenic mice by using a tissue-specific promoter and other regulatory elements. An rHSA expression vector was constructed bearing the cDNA and first intron of HSA under the control of bovine αs1-casein promoter with a 2 × chicken β-globin insulator in the front. Transgenic mice were generated and reverse transcription polymerase chain reaction showed that rHSA was expressed only in the mammary gland, indicating the tissue specificity of the bovine αs1-casein promoter in directing transgene transcription in transgenic mice. Enzyme-linked immunosorbent assay test showed that rHSA was successfully secreted into the milk of transgenic mice with the highest level at 1.98 ± 0.12 g/L. Our results indicate the ability of the bovine αs1-casein promoter to induce successful expression of rHSA in the mammary gland of transgenic mice.